SNORD116 deletions cause Prader‐Willi syndrome with a mild phenotype and macrocephaly. Issue 4 (30th March 2017) - Fontana, P.; Grasso, M.; Acquaviva, F.; Gennaro, E.; Galli, M.L.; Falco, M.; Scarano, F.; Scarano, G.; Lonardo, F.
Abstract : Prader‐Willi syndrome is a complex condition caused by lack of expression of imprinted genes in the paternally derived region of chromosome 15 (15q11q13). A small number of patients with Prader‐Willi phenotype have been discovered to have narrow deletions, not encompassing the whole critical region, but only the SNORD116 cluster, which includes genes codifying for small nucleolar RNAs. This kind of deletion usually is not detected by the classic DNA methylation analysis test. We present the case of a male patient with a mild Prader‐Willi phenotype and a small deletion including SNORD116, diagnosed by methylation‐sensitive multiplex ligation‐dependent probe amplification (MLPA. The patient showed neonatal hypotonia, hyperphagia, obesity, central hypogonadism, hypothyroidism, strabismus. Stature and intellectual development are within the normal range. The presence of macrocephaly, observed in other cases of SNORD116 deletions as well, is uncommon for the classic phenotype of the syndrome. Abstract :